Hydrogenated block copolymers, hydrogenated block copolymer compositions, films, and laminates

JP2026165480APending Publication Date: 2026-10-14ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025057888
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026165480000014
    Figure 2026165480000014
  • Figure 2026165480000001
    Figure 2026165480000001
  • Figure 2026165480000002
    Figure 2026165480000002
Patent Text Reader

Abstract

The present invention aims to provide a laminate or film containing a hydrogenated block copolymer or a composition thereof that can achieve both good film-forming properties, good adhesive properties (high flexibility), and adhesive stability during long-term bonding (high stress relaxation). [Solution] A hydrogenated block copolymer (a) containing vinyl aromatic monomer units and conjugated diene monomer units, satisfying specific conditions (1) to (4); <Condition (1)> The content of polymer block (a) mainly composed of vinyl aromatic monomer units is 12% by mass or less; <Condition (2)> The weight-average molecular weight is 250,000 or less and 30,000 or more; <Condition (3)> It contains at least one hydrogenated copolymer block (b) consisting of vinyl aromatic monomer units and conjugated diene monomer units, and the content of hydrogenated copolymer block (b) is 25% by mass or more; <Condition (4) In viscoelasticity measurement, it has a tanδ peak between 0 and 40°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrogenated block copolymer, a hydrogenated block copolymer composition, a film, and a laminate.

Background Art

[0002] A hydrogenated product of a block copolymer composed of a conjugated diene compound and a vinyl aromatic compound has elasticity similar to that of vulcanized natural rubber or synthetic rubber at normal temperature without vulcanization, and also has processability similar to that of thermoplastic resins at high temperatures, so it is widely used in fields such as plastic modification, adhesives and pressure-sensitive adhesives, automotive parts, and medical instruments. Furthermore, since the hydrogenated product of the block copolymer is excellent in weather resistance and heat resistance, it has been widely put into practical use particularly as automotive parts, medical instruments, building members, and the like.

[0003] Among them, styrene-based elastomers having a random copolymer block composed of a conjugated diene compound and a vinyl aromatic compound are known to have a peak of tanδ (loss tangent) in a specific temperature range and be excellent in stress relaxation properties and low resilience (see, for example, Patent Document 1).

[0004] Further, for example, Patent Document 2 proposes that by using a 4-methyl-1-pentene-based polymer having a peak of tanδ (loss tangent) in a specific temperature range and a hydrogenated styrene-based elastomer, a molded article having a good fit feeling derived from stress relaxation properties can be produced.

[0005] In addition, molded articles that combine both stress relaxation properties and flexibility are regarded as important in applications such as protective films.

[0006] Further, for example, according to Patent Document 3, conventionally, in response to the enforcement of the Act on Promotion of Quality of Watertight and Airtight Houses (houses with excellent waterproofness and airtightness) and the energy saving accompanying the high airtightness and high thermal insulation of houses, waterproof and / or airtight pressure-sensitive adhesive tapes for waterproofing and airtightness have been used in gaps between housing structures and members, between members (mainly, around sash openings, joint portions such as overlapping portions of moisture-permeable waterproof sheets, etc.). In this application, it is required to exhibit waterproofness and airtightness over a long period of time, as well as followability to the movement of housing structures and various members.

[0007] Further, as films for protecting painted surfaces and vehicle bodies from stone chipping, scratches, dents, etc., chipping-resistant films, paint protection films, and vehicle exterior protection films are required to have stretchability (flexibility) that easily follows the curves of the outer surface of the vehicle during application (see, for example, Patent Document 4).

Prior Art Documents

Patent Documents

[0008]

Patent Document 1

Patent Document 2

Patent Document 3

Patent Document 4

Summary of Invention

Problem to be Solved by the Invention

[0009] However, conventional materials have a problem in achieving both higher flexibility and higher stress relaxation properties. In particular, when conventional materials are formed into films or sheets, there is a problem in achieving both good applicability of the film (high flexibility) in applications such as protective films and adhesion stability during long-term application of the film (suppression of lifting due to high stress relaxation properties) while maintaining good film formability. Therefore, the present invention aims to provide a laminate or film containing a hydrogenated block copolymer or a composition thereof that can achieve both good film-forming properties, good adhesive properties (high flexibility), and adhesive stability during long-term bonding (high stress relaxation). [Means for solving the problem]

[0010] As a result of diligent research to solve the above problems, the present inventors have found that by using a hydrogenated block copolymer or composition thereof containing a vinyl aromatic monomer and a conjugated diene monomer unit that meet specific conditions, it is possible to achieve the above performance while maintaining good film-forming properties.

[0011] In other words, the present invention is as follows. [1] It contains vinyl aromatic monomer units and conjugated diene monomer units, A hydrogenated block copolymer (i) that satisfies the following conditions (1) to (4); <Condition (1)>: In the hydrogenated block copolymer (i), the content of polymer block (a) mainly composed of vinyl aromatic monomer units is 12% by mass or less. <Condition (2)>: The weight-average molecular weight (Mw) of the hydrogenated block copolymer (a) is 250,000 or less and 30,000 or more. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) consisting of vinyl aromatic monomer units and conjugated diene monomer units, and the content of hydrogenated copolymer block (b) in the hydrogenated block copolymer (a) is 25% by mass or more. <Condition (4)>: The hydrogenated block copolymer (a) has a tanδ peak between 0 and 40°C in viscoelasticity measurement (1 Hz). [2] The hydrogenated block copolymer (i) according to [1], wherein the content of hydrogenated copolymer block (b) in the hydrogenated block copolymer (i) is 40% by mass or more and 97% by mass or less. [3] A hydrogenated block copolymer (a) described in [1] or [2], A hydrogenated block copolymer (b) containing vinyl aromatic monomer units and conjugated diene monomer units, and / or an olefin resin or olefin elastomer (c), The hydrogenated block copolymer (b) satisfies the following condition (5): A hydrogenated block copolymer composition in which the mass ratio ((a) / ((b)+(c))) of the content of the hydrogenated block copolymer (a) to the total content of the hydrogenated block copolymer (b) and the olefin resin (c) is 5 / 95 to 95 / 5; <Condition (5)> The hydrogenated block copolymer (b) contains at least one polymer block (a) mainly composed of vinyl aromatic monomer units, and the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (b) is greater than 12% by mass. [4] The hydrogenated block copolymer composition according to [3], wherein the mass ratio ((a) / ((b)+(c))) of the content of the hydrogenated block copolymer (a) to the total content of the hydrogenated block copolymer (b) and the olefin resin or olefin elastomer (c) is 40 / 60 to 80 / 20. [5] [1] or [2] contains 5% by mass or more of the hydrogenated block copolymer (a) described above, The tensile modulus is 500 MPa or less. A film with a thickness of 20 μm or more and 2000 μm or less. [6] The following conditions (7) and (8) must be met, A laminate comprising a layer (I) and a resin composition layer (II); <Condition (7)>: The layer (I) contains the hydrogenated block copolymer (a) described in [1] or [2], <Condition (8)>: The outermost or innermost layer must contain 95% by mass or more of an olefin resin or olefin elastomer (c). [7] [1] or [2] contains 20% by mass or more of the hydrogenated block copolymer (a) described above, The tensile modulus is 500 MPa or less. A film with a thickness of 50 μm or more and 1000 μm or less. [8] A layer (I) comprising the hydrogenated block copolymer (a) described in [1] or [2], A resin composition layer (II) and, A laminate with a thickness of 300 μm or less. [Effects of the Invention]

[0012] According to the present invention, it is possible to provide a hydrogenated block copolymer, or a laminate or film containing a composition thereof, that can achieve both good film-forming properties, good adhesive properties (high flexibility), and adhesive stability during long-term bonding (high stress relaxation). [Brief explanation of the drawing]

[0013] [Figure 1] These are the sound pressure level measurement results at each frequency for the films of Example 55 and Comparative Examples 7-8. [Modes for carrying out the invention]

[0014] The following describes in detail embodiments for carrying out the present invention (hereinafter referred to as "this embodiment"). It should be noted that this embodiment is illustrative for explaining the present invention and is not intended to limit the present invention to the following content; the present invention can be implemented in various modified forms within the scope of its gist.

[0015] [Hydrogenated block copolymer] The hydrogenated block copolymer (a) of this embodiment contains vinyl aromatic monomer units and conjugated diene monomer units, and satisfies the following conditions (1) to (4). <Condition (1)>: In the hydrogenated block copolymer (i), the content of polymer block (a) mainly composed of vinyl aromatic monomer units is 12% by mass or less. <Condition (2)>: The weight-average molecular weight (Mw) of the hydrogenated block copolymer (a) is 250,000 or less and 30,000 or more. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) consisting of vinyl aromatic monomer units and conjugated diene monomer units, and the content of hydrogenated copolymer block (b) in the hydrogenated block copolymer (a) is 25% by mass or more. <Condition (4)>: The hydrogenated block copolymer (a) has a tanδ peak between 0 and 40°C in viscoelasticity measurement (1 Hz). The hydrogenated block copolymer (a) of this embodiment, with the above configuration, is able to achieve both good film-forming properties, good adhesive properties (high flexibility), and adhesive stability during long-term application (high stress relaxation), and also has the effect of reducing sound emitted from the film itself (noise suppression).

[0016] (Vinyl aromatic monomer units) The hydrogenated block copolymer (a) of this embodiment contains vinyl aromatic monomer units. The vinyl aromatic compounds that form vinyl aromatic monomer units are not limited to the following, but examples include monomer units derived from styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, and the like. In particular, styrene is preferred from the viewpoint of balancing cost and the mechanical strength of the resin composition containing the hydrogenated block copolymer. These may be used individually or in combination of two or more types.

[0017] (Conjugated diene monomer units) The hydrogenated block copolymer (a) of this embodiment contains conjugated diene monomer units. A conjugated diene monomer unit is a monomer unit derived from a diolefin that has one pair of conjugated double bonds. Examples of such diolefins include, but are not limited to, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, and 1,3-hexadiene. In particular, 1,3-butadiene and isoprene are preferred from the viewpoint of balancing good moldability and mechanical strength. These may be used individually or in combination of two or more types.

[0018] (Amount of vinyl binding in the total conjugated diene monomer unit) In this embodiment, the amount of vinyl bonded in the total conjugated diene monomer unit of the hydrogenated block copolymer (a) is not particularly limited, but is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. In this embodiment, the upper limit of the amount of vinyl bonded in the total conjugated diene monomer unit of the hydrogenated block copolymer (a) is not particularly limited, but is, for example, 85% by mass or less. In this specification, "vinyl bond amount" refers to the total amount of conjugated diene monomer units linked to the total conjugated diene by 1,2-vinyl bonds (conjugated dienes incorporated into the polymer by 1,2-bonds) and 3,4-vinyl bonds (conjugated dienes incorporated into the polymer by 3,4-bonds) (however, if 1,3-butadiene is used as the conjugated diene, it refers to the 1,2-vinyl bond amount), and is a concept that includes the state in which the 1,2-vinyl bonds or 3,4-vinyl bonds are subsequently hydrogenated to become single bonds. That is, although "vinyl" is a name that represents the state of double bonds, "vinyl bond amount" in this specification includes the amount of bonds in which so-called vinyl bonds are hydrogenated to become single bonds. When measured in the manufacturing process of a hydrogenated block copolymer, the total amount of 1,2-vinyl bonds and 3,4-vinyl bonds relative to the total conjugated diene measured before the hydrogenation process corresponds to the "vinyl bond amount". If the amount of vinyl bonds in the total conjugated diene monomer units of the hydrogenated block copolymer (a) is 5% by mass or more, the precipitation of the hydrogenated conjugated diene block from the solution due to crystallization can be suppressed during the hydrogenation process. The amount of vinyl bond in the total conjugated diene monomer unit of the hydrogenated block copolymer (a) can be controlled to the above numerical range by using a modifier such as a tertiary amine compound or ether compound, as described later. The amount of vinyl bonds in the total conjugated diene monomer units of the hydrogenated block copolymer (a) can be measured by nuclear magnetic resonance (NMR) using the block copolymer before hydrogenation as a sample, or by an infrared spectrophotometer as described in the examples below. Furthermore, in nuclear magnetic resonance (NMR) measurements using the hydrogenated block copolymer as a sample, it can be calculated by counting the total number of structures that have been hydrogenated and become single-bonded in addition to the unhydrogenated vinyl structures.

[0019] (Content of total vinyl aromatic monomer units) In this embodiment, the hydrogenated block copolymer (a) preferably has a vinyl aromatic monomer unit content of 20% by mass or more and 80% by mass or less, and more preferably 25% by mass or more and 70% by mass or less. When the vinyl aromatic monomer unit content of the hydrogenated block copolymer (a) of this embodiment is within the above range, it tends to maintain good film-forming properties while further improving both good adhesive properties (high flexibility) and adhesive stability (high stress relaxation) during long-term adhesion of the film. The total vinyl aromatic monomer unit content in the hydrogenated block copolymer (a) of this embodiment can be measured using an ultraviolet spectrophotometer with samples of the block copolymer before hydrogenation and the hydrogenated block copolymer after hydrogenation. Furthermore, the total vinyl aromatic monomer content of the hydrogenated block copolymer (a) can be controlled within the above numerical range mainly by adjusting the amount of vinyl aromatic compound added to the polymerization reactor, the reaction temperature, and the reaction time.

[0020] In this specification, "mainly" in the composition of a hydrogenated block copolymer means that the proportion of each constituent unit in the predetermined block polymer or polymer block is 85% by mass or more, preferably 90% by mass or more, and more preferably 95% by mass or more. Furthermore, since the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 79% by mass or less, the polymer block (a) and the hydrogenated polymer block (b) can be clearly distinguished.

[0021] (Polymer block mainly composed of vinyl aromatic monomer units (a)) In this embodiment, the hydrogenated block copolymer (a) contains 12% by mass or less of polymer blocks (a) (hereinafter also simply referred to as "polymer block (a)") mainly composed of vinyl aromatic monomer units. This prevents pellet blocking. Furthermore, the hydrogenated block copolymer (i) of this embodiment preferably contains 1% by mass or more of polymer block (a), more preferably 2% by mass or more, and more preferably 3% by mass or more. Furthermore, the hydrogenated block copolymer (i) of this embodiment more preferably contains 11% by mass or less of polymer block (a), and even more preferably 10% by mass or less. When the content of polymer blocks (a) mainly composed of vinyl aromatic monomer units is 1% by mass or more, the blocking resistance of the pellets of the hydrogenated block copolymer (i) is good. Furthermore, if the polymer block (a) content is 2% by mass or more, better blocking resistance is exhibited, and if the polymer block (a) content is 3% by mass or more, even better blocking resistance is exhibited. Furthermore, if the content of polymer block (a) mainly composed of vinyl aromatic monomer units is 12% by mass or less, the hydrogenated block copolymer composition described later exhibits good flexibility, improving the adhesiveness during film and sheet application in protective film applications and the like. Furthermore, when the polymer block (a) is present on only one side of the block structure, stress relaxation tends to improve, and high adhesion stability can be achieved during long-term adhesion after film / sheet application in protective film applications, etc.

[0022] The content of polymer block (a) in the hydrogenated block copolymer (i) of this embodiment can be measured using nuclear magnetic resonance (NMR) spectrometers (as described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981); hereafter referred to as the "NMR method") with the block copolymer before hydrogenation or the hydrogenated block copolymer after hydrogenation as samples. Specifically, it can be measured by the method described in the examples below. Furthermore, the content of polymer block (a) in hydrogenated block copolymer (i) can be controlled within the above numerical range mainly by adjusting the amount of vinyl aromatic compound added to the polymerization reactor, the reaction temperature, and the reaction time.

[0023] (Hydrogenated copolymer block (b)) The hydrogenated block copolymer (a) of this embodiment contains at least one hydrogenated copolymer block (b) (hereinafter also simply referred to as "hydrogenated copolymer block (b)") which consists of vinyl aromatic monomer units and conjugated diene monomer units. The hydrogenated copolymer (a) contains 25% by mass or more of the hydrogenated copolymer block (b), preferably 25% by mass or more and 97% by mass or less, more preferably 40% by mass or more and 97% by mass or less, even more preferably 40% by mass or more and 88% by mass or less, and even more preferably 60% by mass or more. When the hydrogenated copolymer (a) contains 25% by mass or more of hydrogenated copolymer block (b), the hydrogenated block copolymer composition described later exhibits high stress relaxation properties, resulting in high adhesion stability during long-term application of films and sheets in protective film applications, and also has a noise reduction effect from the film itself. When the hydrogenated copolymer (a) contains 40% by mass or more, or 60% by mass or more of hydrogenated copolymer block (b), this adhesion stability effect is further improved, and the noise reduction effect from the film itself tends to improve even further.

[0024] The content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) is 79% by mass or less, preferably 40% by mass or more and 75% by mass or less, and more preferably 50% by mass or more and 70% by mass or less. The content of vinyl aromatic monomer units in hydrogenated copolymer block (b) can be measured by nuclear magnetic resonance (NMR) or the like. Furthermore, the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) can be controlled within the above numerical range by adjusting the amount of vinyl aromatic compound and conjugated diene added to the polymerization reactor, the reaction temperature, etc.

[0025] (Hydrogenated polymer block mainly composed of conjugated diene monomer units (c)) The hydrogenated block copolymer (a) of this embodiment may contain one or more hydrogenated polymer blocks (c) (hereinafter sometimes referred to as "hydrogenated polymer block (c)") mainly composed of conjugated diene monomer units. The inclusion of hydrogenated polymer blocks (c) in the hydrogenated block copolymer (a) tends to result in the hydrogenated block copolymer composition described later exhibiting good flexibility, improving the adherence during film / sheet application in protective film applications and the like. In this embodiment, the compatibility between the hydrogenated block copolymer (a) and the polyolefin resin or olefin elastomer (c) described later is improved, leading to improved transparency, abrasion resistance, scratch resistance, and low-temperature properties. These properties are particularly important in applications such as paint protection films where these properties are required.

[0026] In this embodiment, the content of hydrogenated polymer block (c) in hydrogenated block copolymer (a) can be measured by the method described in the examples below. Furthermore, the content of hydrogenated polymer block (c) in hydrogenated block copolymer (a) can be controlled within the above numerical range by adjusting the amount of conjugated diene added to the polymerization reactor, the reaction temperature, etc.

[0027] (Weight-average molecular weight of hydrogenated block copolymer (a)) The weight-average molecular weight (Mw) of the hydrogenated block copolymer (a) in this embodiment is 30,000 or more, preferably 45,000 or more, and more preferably 50,000 or more, from the viewpoint of extrusion moldability during pellet production of the hydrogenated block copolymer (a) and obtaining good mechanical strength in the hydrogenated block copolymer composition described later. When the weight-average molecular weight (Mw) of the hydrogenated block copolymer (a) is 30,000 or more, it tends to exhibit good mechanical strength in the hydrogenated block copolymer composition described later. The upper limit of the weight-average molecular weight (Mw) of the hydrogenated block copolymer (a) in this embodiment is 250,000 or less, preferably 230,000 or less, and more preferably 200,000 or less. When the weight-average molecular weight (Mw) of the hydrogenated block copolymer (a) is 250,000 or less, the hydrogenated block copolymer (a) tends to melt more easily during pellet production (extrusion molding), the strands become more stable, and the extrusion moldability tends to improve. The method for controlling the weight-average molecular weight of the hydrogenated block copolymer (a) within the above range is not particularly limited, but examples include controlling the amount of polymerization initiators and modifiers, coupling agents, and polymerization temperature, as described later. The weight-average molecular weight of the hydrogenated block copolymer (a) in this embodiment is determined by measuring it using gel permeation chromatography (GPC) and using a calibration curve (created using the peak molecular weight of standard polystyrene) obtained from measurements of commercially available standard polystyrene.

[0028] (Molecular weight distribution (Mw / Mn) of hydrogenated block copolymer (a)) The molecular weight distribution (Mw / Mn) of the hydrogenated block copolymer (a) in this embodiment is not particularly limited, but is 10 or less, preferably 8 or less, and more preferably 1.10 or less. The lower limit of Mw / Mn is preferably 1 or more, and more preferably 1.01 or more. The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of hydrogenated block copolymer (I) are determined by measuring them using gel permulation chromatography (GPC), and the molecular weight of the peaks in the chromatogram is determined using a calibration curve (created using the peak molecular weight of standard polystyrene) obtained from measurements of commercially available standard polystyrene. The molecular weight distribution (Mw / Mn) of hydrogenated block copolymer (I) is determined from the ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn).

[0029] (Hydrogenation rate of double bonds in conjugated diene monomer units in hydrogenated block copolymer (a)) From the viewpoint of obtaining good weather resistance, the hydrogenation rate of the double bonds of the conjugated diene monomer units in the hydrogenated block copolymer (a) of this embodiment is preferably 20% or more, more preferably 50% or more, and even more preferably 92% or more. The upper limit of the hydrogenation rate of the double bonds of the conjugated diene monomer units in the hydrogenated block copolymer (a) is not particularly limited, but for example, it is 100% or less. The hydrogenation rate of the double bonds of the conjugated diene monomer units in the hydrogenated block copolymer (a) can be controlled within the above numerical range by adjusting the amount of hydrogenation. In this embodiment, the hydrogenation rate (hydrogenation rate) of the hydrogenated block copolymer (a) can be measured using a nuclear magnetic resonance spectrometer (NMR) or the like.

[0030] (Hydrogenation rate of aromatic double bonds in vinyl aromatic monomer units in hydrogenated block copolymer (a)) The hydrogenation rate of the aromatic double bonds of the vinyl aromatic monomer units in the hydrogenated block copolymer (a) of this embodiment is not particularly limited, but is preferably 50% or less, more preferably 30% or less, and even more preferably 10% or less. The lower limit of the hydrogenation rate of the aromatic double bonds of the vinyl aromatic monomer units in the hydrogenated block copolymer (a) is not particularly limited, but is, for example, 0% or more. The hydrogenation rate of aromatic double bonds in vinyl aromatic monomer units in hydrogenated block copolymer (a) can be measured using nuclear magnetic resonance (NMR) or the like.

[0031] <Structure of hydrogenated block copolymer (I)> The structure of the hydrogenated block copolymer (I) is not particularly limited, and examples thereof include those having a structure represented by the following general formula. (b-c) n , c-(b-c) n , b-(c-b) n , (b-c) m -X, (c-b) m -X, c-(b-a) n , c-(a-b) n , c-(a-b-a) n , c-(b-a-b) n , c-(b-c-a) n , a-(c-b-c-a) n , a-c-(b-a) n , a-c-(a-b) n , a-c-(b-a) n -b, [(a-b-c) n m -X, [a-(b-c) n m -X, [(a-b) n -c] m -X, [(a-b-a) n -c] m -X, [(b-a-b) n -c] m -X, [(c-b-a) n m -X, [c-(b-a) n m -X, [c-(a-b-a) n m-X, [c-(b-a-b) n m -X. In each of the above general formulas, a represents a polymer block (a) mainly composed of vinyl aromatic monomer units, b represents a hydrogenated copolymer block (b) composed of vinyl aromatic monomer units and conjugated diene monomer units, and c represents a hydrogenated polymer block (c) mainly composed of conjugated diene monomer units. n is an integer of 1 or more, preferably an integer of 1 to 5. m is an integer of 2 or more, preferably an integer of 2 to 11. ​​​​​X represents a residue of a coupling agent or a residue of a polyfunctional initiator.

[0032] (tanδ (loss tangent) peak temperature in the viscoelasticity measurement chart of hydrogenated block copolymer (a)) In this embodiment, the hydrogenated block copolymer (a) exhibits at least one tanδ (loss tangent) peak in a viscoelasticity measurement (1 Hz) chart between 0 and 40°C, preferably between 2 and 35°C, and more preferably between 4 and 30°C. This tanδ peak is attributed to the hydrogenated copolymer block (b) in the hydrogenated block copolymer (a). The presence of at least one such peak in the 0 to 40°C range is useful for ultimately obtaining high stress relaxation properties in the desired hydrogenated block copolymer composition. There are no particular limitations on the method for obtaining a hydrogenated block copolymer (a) having a tanδ peak between 0 and 40°C in viscoelasticity measurements (1 Hz). For example, it is particularly effective to increase the content of vinyl aromatic monomer units in the hydrogenated copolymer block (b) and to increase the amount of vinyl bonds in the hydrogenated copolymer block (b). Another example is a method of controlling the tanδ peak temperature (°C) by adjusting the copolymerizability of the vinyl aromatic compound and the conjugated diene by adjusting the polymerization conditions described later. The tanδ of hydrogenated block copolymer (a) can be measured using a viscoelasticity measuring device (ARES, manufactured by TA Instruments Co., Ltd.) under the conditions of a strain of 0.5%, a frequency of 1 Hz, and a heating rate of 3°C / min. Specifically, it can be measured by the method described in the examples below.

[0033] (Other examples of the structure of hydrogenated block copolymer (a)) The structure of the hydrogenated block copolymer (a) in this embodiment is not particularly limited, but examples include having a structure represented by the following general formula. aba, (ab) n -X, c-(ba) n , c-(ab) n , c-(aba) n , c-(bab) n, c-(bca) n a-(cbca) n , ac-(ba) n , ac-(ab) n , ac-(ba) n -b, ca-(ba) n -c, ac-(ba) n -c, ab-(ca) n -b, ac-(bc) n -ac, c-(abc) n -ac, a-(cb) n -ca, c-(ac) n -bcac, [(abc)] n ] m -X, [a-(bc)] n ] m -X, [(ab) n -c] m -X, [(aba) n -c] m -X, [(bab) n -c] m -X, [(cba) n ] m -X, [c-(ba)] n ] m -X, [c-(aba)] n ] m -X, [c-(bab)] n ] m -X. In each of the above general formulas, a represents a polymer block (a) mainly composed of vinyl aromatic monomer units, b represents a hydrogenated copolymer block (b) consisting of vinyl aromatic monomer units and conjugated diene monomer units, and c represents a hydrogenated polymer block (c) mainly composed of conjugated diene monomer units. n is an integer greater than or equal to 1, preferably an integer between 1 and 5. m is an integer greater than or equal to 2, preferably an integer between 2 and 11. X represents a residue of a coupling agent or a residue of a polyfunctional initiator.

[0034] [Method for producing hydrogenated block copolymer (a)] The hydrogenated block copolymer (a) of this embodiment, which is the block copolymer before hydrogenation, can be obtained, for example, by carrying out living anionic polymerization of a vinyl aromatic compound and a conjugated diene compound in a hydrocarbon solvent using a polymerization initiator such as an organoalkali metal compound.

[0035] (Hydroxide solvent) Examples of hydrocarbon solvents include, but are not limited to, aliphatic hydrocarbons such as n-butane, isobutane, n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclohexane, cycloheptane, and methylcycloheptane; and aromatic hydrocarbons such as benzene, toluene, xylene, and ethylbenzene.

[0036] (Polymerization initiator) Polymerization initiators are not particularly limited, but examples include organoalkali metal compounds such as aliphatic hydrocarbon alkali metal compounds, aromatic hydrocarbon alkali metal compounds, and organic aminoalkali metal compounds, which are known to have anionic polymerization activity with respect to vinyl aromatic compounds and conjugated dienes. The organoalkali metal compounds are not limited to the following, but for example, aliphatic and aromatic hydrocarbon lithium compounds having 1 to 20 carbon atoms are preferred, and compounds containing one lithium atom per molecule, dilithium compounds, trilithium compounds, and tetralithium compounds containing multiple lithium atoms per molecule can be applied. Specifically, examples include reaction products of n-propyllithium, n-butyllithium, sec-butyllithium, tert-butyllithium, n-pentyllithium, n-hexyllithium, benzyllithium, phenyllithium, tolyllithium, diisopropenylbenzene and sec-butyllithium, and reaction products of divinylbenzene, sec-butyllithium and a small amount of 1,3-butadiene. Furthermore, organoalkali metal compounds disclosed in, for example, U.S. Patent No. 5,708,092, British Patent No. 2,241,239, and U.S. Patent No. 5,527,753 can also be applied.

[0037] (Adjusting agent) When copolymerizing a vinyl aromatic compound and a conjugated diene using an organoalkali metal compound as a polymerization initiator, the content of vinyl bonds (1,2-bonds or 3,4-bonds) originating from the conjugated diene incorporated into the polymer, as well as the random copolymerization properties of the vinyl aromatic compound and the conjugated diene, can be adjusted by using a predetermined modifier. Examples of such modifying agents include, but are not limited to, tertiary amine compounds, ether compounds, and metal alkoxide compounds. The adjusting agent may be used alone or in combination of two or more types.

[0038] Examples of tertiary amine compounds include, but are not limited to, compounds represented by the general formula: R1R2R3N (where R1, R2, and R3 represent hydrocarbon groups having 1 to 20 carbon atoms or hydrocarbon groups having a tertiary amino group). Specifically, examples include, but are not limited to, trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N-ethylpiperidine, N-methylpyrrolidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, 1,2-dipiperidinoethane, trimethylaminoethylpiperazine, N,N,N',N”,N”-pentamethylethylenetriamine, N,N'-dioctyl-p-phenylenediamine, and the like.

[0039] The ether compounds are not limited to those listed below, but examples include linear ether compounds and cyclic ether compounds. Examples of linear ether compounds include, but are not limited to, dimethyl ether, diethyl ether, diphenyl ether, ethylene glycol diethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, and other ethylene glycol dialkyl ether compounds, as well as diethylene glycol dialkyl ether compounds, such as diethylene glycol diethyl ether, diethylene glycol dibutyl ether, and other diethylene glycol dialkyl ether compounds. Examples of cyclic ether compounds include, but are not limited to, tetrahydrofuran, dioxane, 2,5-dimethyloxolane, 2,2,5,5-tetramethyloxolane, 2,2-bis(2-oxolanyl)propane, and alkyl ethers of furfuryl alcohol.

[0040] Examples of metal alkoxide compounds include, but are not limited to, sodium t-pentoxide, sodium t-butoxide, potassium t-pentoxide, and potassium t-butoxide.

[0041] (Polymerization method) Conventional known methods can be applied as methods for polymerizing vinyl aromatic compounds and conjugated dienes using organoalkali metal compounds as polymerization initiators. The following are some examples, but the method may be batch polymerization, continuous polymerization, or a combination thereof. Batch polymerization is particularly preferred for obtaining copolymers with excellent heat resistance. The polymerization temperature is preferably between 0°C and 180°C, and more preferably between 30°C and 150°C. The polymerization time varies depending on the conditions, but is usually within 48 hours, and preferably between 0.1 and 10 hours. Furthermore, an inert gas atmosphere such as nitrogen gas is preferred as the atmosphere for the polymerization system. The polymerization pressure should be set to a pressure range that can maintain the monomer and solvent in the liquid phase within the above temperature range, and is not particularly limited. Furthermore, it is preferable to take care to prevent the polymerization system from containing impurities that would deactivate the catalyst and living polymer, such as water, oxygen, or carbon dioxide.

[0042] Furthermore, at the end of the polymerization process described above, a coupling reaction may be carried out by adding the necessary amount of a coupling agent with two or more functionalities. As bifunctional coupling agents, known ones can be used and are not limited to the following, but examples include alkoxysilane compounds such as trimethoxysilane, triethoxysilane, tetramethoxysilane, tetraethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane, dichlorodimethoxysilane, dichlorodiethoxysilane, trichloromethoxysilane, and trichloroethoxysilane; dihalogen compounds such as dichloroethane, dibromoethane, dimethyldichlorosilane, and dimethyldibromosilane; and acid esters such as methyl benzoate, ethyl benzoate, phenyl benzoate, and phthalates. Furthermore, while conventionally known polyfunctional coupling agents with three or more functions can be used and are not particularly limited, examples include polyalcohols with three or more functions, epoxidized soybean oil, diglycidylbisphenol A, and polyvalent epoxy compounds such as 1,3-bis(N-N'-diglycidylaminomethyl)cyclohexane; general formula R4-nSiX n Silicon halide compounds represented by (where R is a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, and n is an integer from 3 to 4), such as methylsilyl trichloride, t-butylsilyl trichloride, silicon tetrachloride, and their brominateds; general formula R4-nSnX n Examples of tin halogen compounds represented by (where R is a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, and n is an integer from 3 to 4) include polyvalent halogen compounds such as methyltin trichloride, t-butyltin trichloride, and tin tetrachloride. Dimethyl carbonate and diethyl carbonate may also be used.

[0043] (Modification process) As described above, the hydrogenated block copolymer (a) of this embodiment may be a modified block copolymer to which a group of atoms having a functional group is bonded. It is preferable to bond the group of atoms having a functional group as a step before the hydrogenation step described later. The aforementioned "atomic group having a functional group" is not limited to the following, but examples include atomic groups containing at least one functional group selected from hydroxyl group, carboxyl group, carbonyl group, thiocarbonyl group, acid halide group, acid anhydride group, carboxylic acid group, thiocarboxylic acid group, aldehyde group, thioaldehyde group, carboxylic acid ester group, amide group, sulfonic acid group, sulfonic acid ester group, phosphoric acid group, phosphoric acid ester group, amino group, imino group, nitrile group, pyridyl group, quinoline group, epoxy group, thioepoxy group, sulfide group, isocyanate group, isothiocyanate group, silicon halide group, silanol group, alkoxysilicon group, tin halide group, boronic acid group, boron-containing group, boronic acid base, alkoxytin group, phenyltin group, etc. In particular, atomic groups having at least one functional group selected from hydroxyl group, epoxy group, amino group, silanol group, and alkoxysilane group are preferred. The aforementioned "atomic group having a functional group" can be bonded by a denaturing agent. Examples of denaturing agents include, but are not limited to, tetraglycidylmetoxylendiamine, tetraglycidyl-1,3-bisaminomethylcyclohexane, ε-caprolactone, δ-valerolactone, 4-methoxybenzophenone, γ-glycidoxyethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyldimethylphenoxysilane, bis(γ-glycidoxypropyl)methylpropoxysilane, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, and N-methylpyrrolidone.

[0044] Modified block copolymers are not particularly limited, but can be obtained, for example, by anionic living polymerization using a polymerization initiator having a functional group or an unsaturated monomer having a functional group, by forming a functional group at the living end, or by adding a modifying agent containing a functional group. Other methods for obtaining modified block copolymers include reacting a block copolymer with an organolithium compound or other organolalkali metal compound (metallation reaction), and then adding a functional modifier to the block polymer to which the organolalkali metal has been added. However, in the latter method, a modified hydrogenated block copolymer can also be produced by first obtaining a hydrogenated block copolymer (a), then subjecting it to a metallation reaction, and finally reacting it with a modifying agent. The temperature at which the denaturation reaction is carried out is preferably 0 to 150°C, and more preferably 20 to 120°C. The time required for the denaturation reaction varies depending on other conditions, but is preferably within 24 hours, and more preferably 0.1 to 10 hours. Depending on the type of denaturing agent used, amino groups may generally be converted into organometallic salts at the stage of reaction with the denaturing agent. In such cases, they can be converted back to amino groups by treatment with a compound containing active hydrogen, such as water or alcohol. Furthermore, in such modified block copolymers, some unmodified block copolymers may be present within the modified block copolymer.

[0045] Furthermore, the modified block copolymer described above may be a secondary modified block copolymer. A secondary modified block copolymer is obtained by reacting a modified block copolymer with a secondary modifying agent that is reactive with the functional groups of the modified block copolymer. The secondary modifying agent is not particularly limited, but examples include modifying agents having a functional group selected from a carboxyl group, an acid anhydride group, an isocyanate group, an epoxy group, a silanol group, and an alkoxysilane group, and having at least two of these functional groups. However, if the functional group is an acid anhydride group, it may have one acid anhydride group.

[0046] As described above, when reacting a modified block copolymer with a secondary modifier, the amount of secondary modifier used per equivalent of functional groups bonded to the modified block copolymer is preferably 0.3 to 10 moles, more preferably 0.4 to 5 moles, and even more preferably 0.5 to 4 moles. The method for reacting the modified block copolymer with the secondary modifier is not particularly limited and any known method can be applied. For example, this could be the melt-kneading method described later, or a method in which each component is dissolved or dispersed in a solvent and mixed before reaction. It is preferable to carry out these secondary modifications after the hydrogenation step.

[0047] Suitable secondary modifiers include, but are not limited to, maleic anhydride, pyromellitic anhydride, 1,2,4,5-benzenetetracarboxylic dianhydride, toluene diisocyanate, tetraglycidyl-1,3-bisaminomethylcyclohexane, and bis-(3-triethoxysilylpropyl)-tetrasulfan.

[0048] Furthermore, the hydrogenated block copolymer (a) of this embodiment can be a modified block copolymer obtained by graft modification with an α,β-unsaturated carboxylic acid or its derivatives, such as its anhydride, esterified, amidated, or imidated form. Examples of α,β-unsaturated carboxylic acids or their derivatives include, but are not limited to, maleic anhydride, maleimide anhydride, acrylic acid or its esters, methacrylic acid or its esters, endo-cis-bicyclo[2,2,1]-5-heptene-2,3-dicarboxylic acid or its anhydride. The amount of α,β-unsaturated carboxylic acid or its derivative added is preferably 0.01 to 20 parts by mass, and more preferably 0.1 to 10 parts by mass, per 100 parts by mass of hydrogenated block copolymer (a). The reaction temperature for graft modification is preferably 100 to 300°C, and more preferably 120 to 280°C. The method for graft modification is not particularly limited, but for example, the method described in Japanese Patent Publication No. 62-79211 can be applied.

[0049] (Hydrogenation reaction process) The hydrogenated block copolymer (a) of this embodiment is obtained by subjecting a non-hydrogenated, unmodified or modified block copolymer, as described above, to a hydrogenation reaction using a predetermined hydrogenation catalyst. Examples of hydrogenation catalysts include, but are not limited to, the following: (1) supported heterogeneous hydrogenation catalysts in which metals such as Ni, Pt, Pd, and Ru are supported on carbon, silica, alumina, diatomaceous earth, etc.; (2) so-called Ziegler-type hydrogenation catalysts using organic acid salts of Ni, Co, Fe, Cr, etc. or transition metal salts such as acetylacetone salts and reducing agents such as organoaluminum; and (3) homogeneous hydrogenation catalysts such as so-called organometallic complexes such as organometallic compounds of Ti, Ru, Rh, and Zr. Furthermore, while not limited to the following, hydrogenated catalysts can also be used, for example, those described in Japanese Patent Publication No. 42-8704, Japanese Patent Publication No. 43-6636, Japanese Patent Publication No. 63-4841, Japanese Patent Publication No. 1-37970, Japanese Patent Publication No. 1-53851, and Japanese Patent Publication No. 2-9041. Suitable hydrogenation catalysts include titanocene compounds, reducing organometallic compounds, or mixtures thereof. The titanocene compounds are not limited to those listed below, but for example, compounds described in Japanese Patent Publication No. 8-109219 can be used. Specifically, examples include compounds having at least one ligand with a (substituted) cyclopentadienyl skeleton, an indenyl skeleton, or a fluorenyl skeleton, such as biscyclopentadienyl titanium dichloride and monopentamethylcyclopentadienyl titanium trichloride. Reducing organometallic compounds include, but are not limited to, organolithium and other organoalkali metal compounds, organomagnesium compounds, organoaluminum compounds, organoboron compounds, or organozinc compounds.

[0050] Let's explain hydrogenation reactions. The reaction temperature is generally preferably in the range of 0 to 200°C, and more preferably in the range of 30 to 150°C. The hydrogen pressure used in the hydrogenation reaction is preferably 0.1 to 15 MPa, more preferably 0.2 to 10 MPa, and even more preferably 0.3 to 5 MPa. The hydrogenation reaction time is usually preferably 3 minutes to 10 hours, and more preferably 10 minutes to 5 hours. The hydrogenation reaction may be carried out as a batch process, a continuous process, or a combination of both. It is preferable to remove catalyst residue from the solution of the hydrogenated block copolymer obtained via the hydrogenation reaction, as needed, and separate the hydrogenated block copolymer from the solution. The separation method is not limited to the following, but examples include: adding a polar solvent that is a poor solvent for hydrogenation-modified copolymers, such as acetone or alcohol, to the reaction solution after hydrogenation to precipitate and recover the polymer; immersing the reaction solution in hot water under stirring and removing the solvent by steam stripping to recover the polymer; or directly heating the polymer solution to remove the solvent by distillation.

[0051] Furthermore, the hydrogenated block copolymer (a) of this embodiment may contain stabilizers such as various phenolic stabilizers, phosphorus-based stabilizers, sulfur-based stabilizers, and amine-based stabilizers.

[0052] [Hydrogenated block copolymer composition] The hydrogenated block copolymer composition of this embodiment may also contain, in addition to the hydrogenated block copolymer (a) described above, a hydrogenated block copolymer (b) described later, which contains a vinyl aromatic monomer and a conjugated diene monomer unit, or an olefin resin or olefin elastomer (c). The mass ratio ((a) / ((b)+(c))) of the content of the hydrogenated block copolymer (a) to the total content of the hydrogenated block copolymer (b) and the olefin resin or olefin elastomer (c) is preferably 5 / 95 to 95 / 5, more preferably 20 / 80 to 90 / 10, and even more preferably 40 / 60 to 80 / 20. When the mass ratio ((a) / ((b)+(c))) is 5 / 95 to 95 / 5, the hydrogenated block copolymer composition of this embodiment tends to exhibit good film-forming properties and stress-relaxing properties when formed into sheets or films, and this effect tends to be further enhanced when the mass ratio ((a) / ((b)+(c))) is 20 / 80 to 90 / 10 or 40 / 60 to 80 / 20. Furthermore, when the mass ratio ((a) / ((b)+(c))) falls within the above range, the elongation at break in the hydrogenated block copolymer composition of this embodiment tends to improve. The hydrogenated block copolymer composition of this embodiment may also contain any rubber softener, modifier, additive, etc.

[0053] ((b) Hydrogenated block copolymer) The hydrogenated block copolymer (b) used in this embodiment contains at least one polymer block (a) mainly composed of vinyl aromatic monomer units, the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (b) is more than 12% by mass, and the content of polymer block (a) in the hydrogenated block copolymer (b) is preferably 80% by mass or less, and more preferably 15% by mass or more and 70% by mass or less. Furthermore, the content of polymer block (a) in hydrogenated block copolymer (b) can be controlled within the above numerical range mainly by adjusting the amount of vinyl aromatic compound added to the polymerization reactor, the reaction temperature, and the reaction time. In this embodiment, the content of polymer block (a) in hydrogenated block copolymer (b) can be measured using nuclear magnetic resonance (NMR) spectrometers (as described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981); hereafter referred to as the "NMR method") with the block copolymer before hydrogenation and the hydrogenated block copolymer after hydrogenation as samples. Specifically, it can be measured by the method described in the examples below.

[0054] ((h) Olefin resin or olefin elastomer) The olefin resin or olefin elastomer (c) constituting the hydrogenated block copolymer composition of this embodiment will be described below. The olefin resin or olefin elastomer (c) is not limited to the following, but examples include homopolymers of α-olefins such as polyethylene (PE), polypropylene (PP), 1-butene, 1-pentene, 1-hexene, 3-methyl-1-butene, 4-methyl-1-pentene, and 1-octene. Other examples include random copolymers or block copolymers, or olefin elastomers, consisting of combinations of olefins selected from ethylene, propylene, butene, pentene, hexene, octene, etc. Specifically, examples of ethylene and / or propylene-α-olefin copolymers include, but are not limited to, ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-3-methyl-1-butene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene-1-decene copolymer, propylene-1-butene copolymer, propylene-1-hexene copolymer, propylene-1-octene copolymer, propylene-4-methyl-1-pentene copolymer, ethylene-propylene-1-butene copolymer, propylene-1-hexene-ethylene copolymer, and propylene-1-octene-ethylene copolymer. Furthermore, copolymers with ethylene and / or propylene also include copolymers with other unsaturated monomers other than the α-olefins mentioned above. The copolymers with the aforementioned other unsaturated monomers are not limited to the following, but include, for example, copolymers of ethylene and / or propylene with unsaturated organic acids or their derivatives such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, methyl acrylate, methyl methacrylate, maleic anhydride, arylmaleimide, and alkylmaleimide; copolymers of ethylene and / or propylene with vinyl esters such as vinyl acetate; and further, copolymers of ethylene and / or propylene with non-conjugated dienes such as dicyclopentadiene, 4-ethylidene-2-norbornene, 4-methyl-1,4-hexadiene, and 5-methyl-1,4-hexadiene.

[0055] Furthermore, the olefin resin or olefin elastomer (c) may be modified with a predetermined functional group. The functional groups are not particularly limited, but examples include epoxy groups, carboxyl groups, acid anhydride groups, hydroxyl groups, and the like. The following compounds are examples of functional group-containing compounds or modifiers used to modify olefin resins or olefin elastomers (c). Examples include unsaturated epoxides such as glycidyl methacrylate, glycidyl acrylate, vinyl glycidyl ether, and allyl glycidyl ether, as well as unsaturated organic acids such as maleic acid, fumaric acid, itaconic acid, citraconic acid, allyl succinic acid, maleic anhydride, fumaric anhydride, and itaconic anhydride. Other examples, though not particularly limited, include ionomers and chlorinated polyolefins.

[0056] The rubber softener softens the hydrogenated block copolymer composition of this embodiment and imparts fluidity (moldability). The rubber softener can be, but is not limited to, mineral oil or liquid or low molecular weight synthetic softeners, and naphthenic and / or paraffinic process oils or extender oils are particularly preferred. Mineral oil-based rubber softeners are mixtures of aromatic rings, naphthenic rings, and paraffinic chains. Those in which the number of carbon atoms in the paraffinic chain accounts for 50% or more of the total carbon atoms are called paraffinic, those in which the number of carbon atoms in the naphthenic ring accounts for 30-45% are called naphthenic, and those in which the number of aromatic carbon atoms exceeds 30% are called aromatic. The synthetic softener is not particularly limited, and for example, polybutene, low molecular weight polybutadiene, liquid paraffin, etc. can be used, but the mineral oil-based rubber softeners mentioned above are more preferred. When high heat resistance and mechanical properties are required for the hydrogenated block copolymer composition of this embodiment, the mineral oil-based rubber softener used preferably has a kinematic viscosity at 40°C of 60 cst or more, and more preferably 120 cst or more. Rubber softeners may be used individually or in combination of two or more types.

[0057] The modifier shall have the function of improving the scratch resistance of the surface of the hydrogenated block copolymer composition of this embodiment, or improving its tackiness. Examples of modifiers include, but are not limited to, organic polysiloxanes. Organic polysiloxanes exert a surface modification effect on hydrogenated block copolymer compositions and function as an abrasion resistance improvement aid. The modifier can be in any form, from a low-viscosity liquid to a high-viscosity liquid or a solid. However, from the viewpoint of ensuring good dispersibility in the hydrogenated block copolymer composition of this embodiment, a liquid, i.e., silicone oil, is preferred. Furthermore, regarding the kinematic viscosity of the modifier, from the viewpoint of suppressing the bleeding of the polysiloxane itself, 90 cst or higher is preferred, and 1000 cst or higher is more preferred. The polysiloxane is not limited to the following, but examples include general-purpose silicone oils such as dimethylpolysiloxane and methylphenylpolysiloxane, and various modified silicone oils such as alkyl-modified, polyether-modified, fluorine-modified, alcohol-modified, amino-modified, and epoxy-modified. There are no particular limitations, but dimethylpolysiloxane is preferred because it is highly effective as an abrasion resistance improving aid. These modifiers may be used individually or in combination of two or more.

[0058] As additives, there are no particular restrictions as long as they are commonly used in the formulation of thermoplastic resins and rubbery polymers, such as fillers, lubricants, release agents, plasticizers, antioxidants, heat stabilizers, light stabilizers, UV absorbers, flame retardants, antistatic agents, reinforcing agents, and colorants. Examples of fillers include, but are not limited to, inorganic fillers such as silica, talc, mica, calcium silicate, hydrotalcite, kaolin, diatomaceous earth, graphite, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, calcium sulfate, and barium sulfate, as well as organic fillers such as carbon black. Examples of lubricants, though not limited to the following, include stearic acid, behenic acid, zinc stearate, calcium stearate, magnesium stearate, and ethylenebisstearoamide. Examples of plasticizers include, but are not limited to, organic polysiloxanes and mineral oil. Antioxidants include, but are not limited to, hindered phenol antioxidants. Examples of heat stabilizers include, but are not limited to, phosphorus-based, sulfur-based, and amine-based heat stabilizers. Examples of light stabilizers include, but are not limited to, hindered amine-based light stabilizers. Examples of UV absorbers include, but are not limited to, benzotriazole-based UV absorbers. Examples of reinforcing agents include, but are not limited to, organic fibers, glass fibers, carbon fibers, and metal whiskers. Examples of colorants include, but are not limited to, titanium dioxide, iron oxide, and carbon black. Other examples include those listed in "Rubber and Plastic Compounding Chemicals" (edited by Rubber Digest Co., Ltd.).

[0059] [Molded articles using hydrogenated block copolymer compositions] The molded article of this embodiment is a molded article of the hydrogenated block copolymer composition described above. The molded article of this embodiment is not particularly limited, but can be manufactured by methods such as extrusion molding, injection molding, two-color injection molding, sandwich molding, hollow molding, compression molding, vacuum molding, rotational molding, powder slush molding, foam molding, lamination molding, calendering, blow molding, etc. The molded articles of this embodiment are not limited to the following, but include a wide variety of molded articles such as sheets, films, injection-molded articles of various shapes, hollow molded articles, compressed air molded articles, vacuum molded articles, extruded articles, foamed articles, nonwoven fabrics and fibrous molded articles, and synthetic leather. These molded products can be used, for example, in automotive parts, food packaging materials, medical devices, home appliance components, electronic device components, building materials, industrial parts, household goods, toy materials, footwear materials, textile materials, and the like.

[0060] [Film using hydrogenated block copolymer composition] The film of this embodiment contains 5% by mass or more of the above-mentioned hydrogenated block copolymer (a), has a tensile modulus of 500 MPa or less, and has a thickness of 20 μm to 2000 μm. Preferably, the film of this embodiment contains 20% by mass or more of the above-mentioned hydrogenated block copolymer (a), has a tensile modulus of 500 MPa or less, and has a thickness of 50 μm to 1000 μm. In the film of this embodiment, the upper limit of the content of the above-mentioned hydrogenated block copolymer (a) is not particularly limited, but for example, it is 100% by mass or less. The lower limit of the tensile modulus of the film in this embodiment is not particularly limited, but for example, it is 1 MPa or more. The method for controlling the tensile modulus of the film to the aforementioned range is not particularly limited, but examples include lowering the modulus of elasticity of the hydrogenated block copolymer composition, and increasing the stretch during film molding by increasing the winding speed. In this embodiment, the tensile modulus of the film can be measured by the method described in the later examples. The film of this embodiment can be manufactured, for example, using the hydrogenated block copolymer composition described above. The film containing the hydrogenated block copolymer composition may be a single-layer film consisting of a single composition or a multilayer film consisting of multiple compositions. The thickness of the film in this embodiment is preferably 20 μm or more and 2000 μm or less, more preferably 50 μm or more and 1000 μm or less, and even more preferably 80 μm or more and 500 μm or less. The film in this embodiment exhibits good film-forming properties when its thickness is 20 μm or more, and exhibits even better film-forming properties when its thickness is 50 μm or more or 80 μm or more. Furthermore, the film of this embodiment exhibits good flexibility due to its thickness of 2000 μm or less, improving its adherence during film / sheet application in protective film applications, and exhibits even better adherence when its thickness is 1000 μm or less, or 500 μm or less.

[0061] The film in this embodiment may be a multilayer film (laminated structure). The laminate of this embodiment satisfies the following conditions (7) and (8) and includes a layer (I) and a resin composition layer (II). <Condition (7)>: The layer (I) contains the above-mentioned hydrogenated block copolymer (i), <Condition (8)>: The outermost or innermost layer must contain 95% by mass or more of an olefin resin or olefin elastomer (c). In particular, by having a layer (I) containing a hydrogenated block copolymer (a), and a resin composition layer (II) having 95% by mass or more of an olefin resin or olefin elastomer (c) in the outermost or innermost layer, stickiness can be reduced and film dispensing performance can be improved. It is more preferable that the content of olefin resin or olefin elastomer (c) in the outermost or innermost layer be 95% by mass or more and 100% by mass or less. In the resin composition layer (II), in addition to the olefin resin or olefin elastomer (c), fillers, flame retardants, lubricants, weathering agents, weathering aids, etc. may be included. The thickness of the resin composition layer (II) is preferably 2000 μm or less, more preferably 1000 μm or less, even more preferably 500 μm or less, and even more preferably 300 μm or less, from the viewpoint of exhibiting good flexibility. The laminate of this embodiment preferably comprises a layer (I) containing the above-mentioned hydrogenated block copolymer (a) and a resin composition layer (II), and has a thickness of 300 μm or less. Furthermore, from the viewpoint of exhibiting good flexibility, the laminate or single-layer film of this embodiment preferably has a tensile modulus of 1000 MPa or less, more preferably 500 MPa or less, and even more preferably 200 MPa or less.

[0062] The film of this embodiment may include an adhesive layer. Hereafter, a film including an adhesive layer will be referred to as an adhesive film. The adhesive layer of the adhesive film may contain hydrogenated block copolymers, resins, etc. It may also contain tackifiers. The tackifier is not particularly limited as long as it is a resin capable of imparting viscosity to the adhesive layer, but known tackifiers include hydrogenated terpene resins, rosin-based terpene resins, hydrogenated rosin-terpene resins, aromatically modified hydrogenated terpene resins, coumarone resins, phenolic resins, terpene-phenolic resins, hydrogenated terpene-phenolic resins, aromatic hydrocarbon resins, and aliphatic hydrocarbon resins. Hydrogenated terpene resins, aromatically modified hydrogenated terpene resins, hydrogenated terpene-phenolic resins, and terpene-phenolic resins are particularly preferred. The tackifier may be used alone or in a mixture of two or more types. Specifically, tackifiers described in "Rubber and Plastic Compounding Chemicals" (edited by Rubber Digest Co., Ltd.) can be used. By using a tackifier, the adhesive strength can be improved. The content of the tackifier in the adhesive layer is preferably 0.5 to 50% by mass, more preferably 5 to 45% by mass, and even more preferably 10 to 30% by mass. A tackifier content of 50% by mass or less in the adhesive layer is preferable because it effectively prevents excessive adhesion and tends to further reduce the amount of adhesive residue when peeling. A content of 0.5% by mass or more tends to provide a moderate level of adhesion. The adhesive layer may contain other materials as described later.

[0063] [Other materials in the adhesive layer] <Hydrogenated styrene elastomer> The adhesive layer of the adhesive film may further contain a hydrogenated styrene elastomer. Hydrogenated styrene elastomers are not limited to the following, but typical examples include styrene-butadiene-styrene (SBS), styrene-isoprene-styrene (SIS), styrene-butadiene random polymer (SBR), styrene-ethylene-butylene-styrene (SEBS) and styrene-ethylene-propylene-styrene (SEPS), which are obtained by hydrogenating SBS. Other elastomers with structures such as styrene-ethylene-butylene (SEB), styrene-ethylene-propylene (SEP), and styrene-isobutylene-styrene triblock copolymer (SIBS) may also be used. Furthermore, reactive elastomers obtained by imparting various functional groups to the hydrogenated styrene elastomer may also be used. The functional groups are not limited to the following, but examples include hydroxyl groups, carboxyl groups, carbonyl groups, thiocarbonyl groups, acid halide groups, acid anhydride groups, thiocarboxylic acid groups, aldehyde groups, thioaldehyde groups, carboxylic acid ester groups, amide groups, sulfonic acid groups, sulfonic acid ester groups, phosphoric acid groups, phosphoric acid ester groups, amino groups, imino groups, nitrile groups, pyridyl groups, quinoline groups, epoxy groups, thioepoxy groups, sulfide groups, isocyanate groups, isothiocyanate groups, silicon halide groups, alkoxysilicon groups, tin halide groups, boronic acid groups, boron-containing groups, boronic acid bases, alkoxytin groups, and phenyltin groups.

[0064] <Olefin resin or olefin elastomer, olefin elastomer> The adhesive layer of the adhesive film may further contain an olefin resin or an olefin elastomer. The olefin resin or olefin elastomer is not particularly limited, but examples include α-olefin polymers or copolymers having 2 to 20 carbon atoms, and copolymers of ethylene with an unsaturated carboxylic acid or an unsaturated carboxylic acid ester. Specifically, although not particularly limited, examples include ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-4-methylpentene copolymer, ethylene-1-octene copolymer, propylene homopolymer, propylene-ethylene copolymer, propylene-ethylene-1-butene copolymer, 1-butene homopolymer, 1-butene-ethylene copolymer, 1-butene-propylene copolymer, 4-methylpentene homopolymer, 4-methylpentene-1-propylene copolymer, 4-methylpentene-1-butene copolymer, 4-methylpentene-1-propylene-1-butene copolymer, propylene-1-butene copolymer, ethylene-vinyl acetate copolymer, ethylene-methacrylic acid copolymer, ethylene-methyl methacrylate copolymer, and the like.

[0065] <Acrylic copolymer> The adhesive layer of the adhesive film may further contain an acrylic copolymer. The acrylic copolymer is not particularly limited, but examples include copolymers of methyl acrylate, ethyl acrylate, methyl methacrylate, acrylonitrile, etc., with vinyl acetate, vinyl chloride, styrene, etc.

[0066] <Softener> The adhesive layer of the adhesive film may further contain a softening agent. The softening agent is not particularly limited; for example, both mineral oil-based softening agents and synthetic resin-based softening agents can be used. Mineral oil-based softeners are not particularly limited, but examples include mixtures of aromatic hydrocarbons, naphthenic hydrocarbons, and paraffinic hydrocarbons. Paraffinic hydrocarbons in which the number of carbon atoms accounts for 50% or more of the total carbon atoms are called paraffinic oils, naphthenic hydrocarbons in which the number of carbon atoms accounts for 30-45% are called naphthenic oils, and aromatic hydrocarbons in which the number of carbon atoms accounts for 35% or more are called aromatic oils. As mineral oil-based softeners, paraffinic oils used as rubber softeners are preferred, and as synthetic resin softeners, polybutene, low molecular weight polybutadiene, etc., are preferred.

[0067] <Antioxidants, light stabilizers, etc.> The adhesive layer of the adhesive film may further contain stabilizers such as antioxidants and light stabilizers. Antioxidants include, but are not limited to, 2,6-di-t-butyl-4-methylphenol, n-octadecyl-3-(4'-hydroxy-3',5'-di-t-butylphenyl)propionate, 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 2,4-bis[(octylthio)methyl]-o-cresol, 2-t-butyl-6-(3-t-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2,4-di-t- Examples include hindered phenol antioxidants such as mil-6-[1-(3,5-di-t-amyl-2-hydroxyphenyl)ethyl]phenyl acrylate and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)] acrylate; sulfur-based antioxidants such as dilauryl thiodipropionate, lauryl stearyl thiodipropionate, and pentaerythritol-tetrakis(β-lauryl thiopropionate); and phosphorus-based antioxidants such as tris(nonylphenyl) phosphite and tris(2,4-di-t-butylphenyl) phosphite. Examples of light stabilizers include, but are not limited to, benzotriazole-based UV absorbers such as 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-t-butylphenyl)benzotriazole, and 2-(2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole, as well as benzophenone-based UV absorbers such as 2-hydroxy-4-methoxybenzophenone, or hindered amine-based light stabilizers.

[0068] <Pigments, waxes, thermoplastic resins, natural rubber, synthetic rubber> In addition to the above, the adhesive layer of the adhesive film may contain various additives as needed. Examples of the aforementioned additives include, but are not limited to, pigments such as red iron oxide and titanium dioxide; waxes such as paraffin wax, microcrystalline wax, and low molecular weight polyethylene wax; polyolefin-based or low molecular weight vinyl aromatic thermoplastic resins such as amorphous polyolefins and ethylene-ethyl acrylate copolymers; natural rubber; and synthetic rubbers such as polyisoprene rubber, polybutadiene rubber, styrene-butadiene rubber, ethylene-propylene rubber, chloroprene rubber, acrylic rubber, isoprene-isobutylene rubber, and polypentenamer rubber. Examples of the aforementioned synthetic rubbers include those described in "Rubber and Plastic Compounding Chemicals" (edited by Rubber Digest Co., Ltd.), etc.

[0069] <Saturated fatty acid bisamide> The adhesive layer of the adhesive film may contain saturated fatty acid bisamide, which has an effect of suppressing the enhancement of adhesion. Examples of saturated fatty acid bisamides include, but are not limited to, saturated fatty acid aliphatic bisamides such as ethylene bisstearamide (EBSA), methylene bisstearamide, and hexamethylene bisstearamide; and saturated fatty acid aromatic bisamides such as m-xylylene bisstearamide and N,N'-distearyl isophthalamide. These saturated fatty acid bisamides may be used individually or in combination of two or more. Furthermore, the saturated fatty acid bisamide may be blended with a styrene-based block phase reinforcing agent that has the effect of suppressing increased adhesion. Examples of styrene-based block phase reinforcing agents include, but are not limited to, styrene and styrene-based compounds such as α-methylstyrene, p-methylstyrene, p-chlorostyrene, chloromethylstyrene, tert-butylstyrene, p-ethylstyrene, and divinylbenzene, which can be used as monomer units. These may be used individually or in combination of two or more.

[0070] <Method for manufacturing the resin material constituting the adhesive layer of an adhesive film> The resin material constituting the adhesive layer of the adhesive film of this embodiment can be manufactured by dry blending resin and other components, or by mixing them using equipment typically used for mixing polymer materials. The mixing apparatus is not particularly limited, but examples include Banbury mixers, Laboplast mills, single-screw extruders, twin-screw extruders, and other kneading devices. Manufacturing by a melt mixing method using an extruder is preferable from the viewpoint of productivity and good kneading properties. Furthermore, especially when a tackifier is incorporated into the adhesive layer, the dry blending method described above may be used. However, since tackifiers are highly sticky and flake-like, making them difficult to handle, a pre-mixed masterbatch may be prepared. The melting temperature during mixing can be set as appropriate, but is usually within the range of 130 to 300°C, and preferably within the range of 150 to 250°C. The resin material constituting the adhesive layer may be subjected to foaming treatment to achieve weight reduction, flexibility, and improved adhesion. Foaming methods are not limited to the following, but include, for example, chemical methods, physical methods, and the use of thermally expanding microballoons. Bubbles can be distributed within the material by adding chemical foaming agents such as inorganic foaming agents and organic foaming agents, physical foaming agents, or thermally expanding microballoons. Furthermore, weight reduction, flexibility, and improved adhesion may be achieved by adding hollow fillers (pre-inflated balloons).

[0071] <Method for manufacturing adhesive film> The method for manufacturing an adhesive film is not particularly limited, but examples include a method of coating a solution or molten material of the resin material constituting the adhesive layer onto a base film, or a method using a film extruder. In this case, when using a solution or melt of the resin material that constitutes the adhesive layer, it may be used as a solution or melt after being made into a resin composition, or other materials may be mixed with the resin solution or melt. Methods for coating resin material solutions include, but are not limited to, dissolving them in a solvent, coating them onto a substrate film using a coater, and then heating and drying the solvent. Alternatively, methods for melting and coating resin materials include, but are not limited to, coating the molten resin material onto a substrate film using a hot-melt coater. In this case, it is preferable to use various substrate films having a glass transition temperature, melting point, or softening point higher than the coating temperature. The method using a film extruder is not limited to the following, but for example, it involves combining the components of the adhesive layer, which include a resin material, and components such as a thermoplastic resin that can constitute the base film, in a melt co-extruder, creating two separate flows: a fluid for forming the adhesive layer and a fluid for forming the base film. These two flows are merged at the die opening to form a single fluid, which is then extruded to composite the adhesive layer and the resin film layer. In the case of the method using a film extruder, the resin material that forms the adhesive layer can also be manufactured by dry blending the components for the adhesive layer beforehand, making it a highly productive method. Furthermore, when extruded, the resulting adhesive film tends to have particularly excellent adhesion and bonding strength. The adhesive film can be temporarily attached to the surface of optical molded bodies such as light guide plates and prism sheets, synthetic resin plates, metal plates, decorative plywood, coated steel plates, and various nameplates, and can be used as a protective film to prevent scratches and dirt during processing, transportation, and storage of these adherends. [Examples]

[0072] The present invention will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited in any way by the following examples and comparative examples. The methods for measuring and evaluating the physical properties applied to the examples and comparative examples are described below.

[0073] [Method for identifying the structure of hydrogenated block copolymers] ((1) Content of total vinyl aromatic monomer units (styrene) in hydrogenated block copolymer) Using a hydrogenated block copolymer, the total vinyl aromatic monomer unit (styrene) content in the hydrogenated block copolymer was measured using an ultraviolet spectrophotometer (Shimadzu Corporation, UV-2450).

[0074] ((2-1) Content of polymer blocks (polystyrene blocks) (a) mainly composed of vinyl aromatic monomer units in hydrogenated block copolymers) Using hydrogenated block copolymers, the content of polymer blocks (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymers was measured using nuclear magnetic resonance (NMR) spectroscopy (the method described in Y. Tanaka, et al., RUBBER CHEMISTRY and TECHNOLOGY 54, 685 (1981); hereafter referred to as the "NMR method").

[0075] ((2-2) Content of hydrogenated copolymer block (b) in hydrogenated block copolymer) The content of hydrogenated copolymer block (b) in the hydrogenated block copolymer was determined by calculating (100 - content of hydrogenated copolymer block (a) in the hydrogenated block copolymer).

[0076] ((2-3) Content of hydrogenated polymer block (c) in hydrogenated block copolymer) During the polymerization reaction, the mass was calculated from the ratio of the mass of the conjugated diene monomer polymerized alone to the mass of the hydrogenated block copolymer (a).

[0077] ((3) Amount of vinyl bonds in hydrogenated block copolymer) The amount of vinyl bonds was measured using a hydrogenated block copolymer and nuclear magnetic resonance (NMR) spectrometer. The amount of vinyl bonds in the conjugated diene monomer units in the hydrogenated block copolymer was determined by the ratio of the total area of ​​1,2-bonds and 3,4-bonds to the total area of ​​all peaks related to the conjugated diene monomer units (the proportion of 1,2-bonds and 3,4-bonds, and the 1,4-bond peaks) obtained by NMR spectrometer.

[0078] (4) Weight-average molecular weight of hydrogenated block copolymers Hydrogenated block copolymers were used, and measurements were performed using GPC [instrument: HLC-82209PC (Tosoh Corporation), column: TSKgeguard column SuperHZ-L (4.6 mm × 20 cm) × 3]. Tetrahydrofuran was used as the solvent. The measurements were performed at a temperature of 35°C. The weight-average molecular weight of the hydrogenated block copolymer was determined by using a calibration curve (created using the peak molecular weight of standard polystyrene) obtained from measurements of commercially available standard polystyrene, based on the molecular weight of the peaks in the chromatogram. If there were multiple peaks in the chromatogram, the weight-average molecular weight (Mw) of the hydrogenated block copolymer was determined from the molecular weight of each peak and the composition ratio of each peak (determined from the area ratio of each peak in the chromatogram).

[0079] ((5) Hydrogenation rate of double bonds in conjugated diene monomer units of hydrogenated block copolymers) Using hydrogenated block copolymers, the hydrogenation rate of double bonds in the conjugated diene monomer units of the hydrogenated block copolymers was measured using a nuclear magnetic resonance spectrometer (ECS400, JEOL RESONANCE).

[0080] ((6-1) Content of vinyl aromatic monomer units in hydrogenated copolymer block (b) relative to the total hydrogenated block copolymer, Content of vinyl aromatic monomer units in hydrogenated copolymer block (b)) The content of vinyl aromatic monomer units in hydrogenated copolymer block (b) relative to the total polymer was calculated from the difference between the content of total vinyl aromatic monomer units in the hydrogenated block copolymer measured in (1) above and the content of polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer measured in (2-1) above. The content of vinyl aromatic monomer units in hydrogenated copolymer block (b) was then calculated from the ratio of this ratio to the content of hydrogenated copolymer block (b) in the hydrogenated block copolymer measured in (2-2) above.

[0081] ((6-2) Content of conjugated diene monomer units in hydrogenated copolymer block (b) relative to the total hydrogenated block copolymer) This was determined by subtracting the content of vinyl aromatic monomer units in hydrogenated copolymer block (b) relative to the total content of hydrogenated copolymer block (b) from the content of hydrogenated copolymer block (b) in the hydrogenated copolymer block (b).

[0082] [Method for measuring the physical properties of hydrogenated block copolymers] ((7) tanδ peak temperature) As described later, the "press-molded hydrogenated block copolymer sheet" was cut to a size of 12.5 mm in width and 40 mm in length to be used as a sample for measurement. Next, this measurement sample was set in the torsion-type geometry of the ARES instrument (manufactured by TA Instruments Co., Ltd., product name), and the tanδ peak temperature from -20 to 60°C was determined under the conditions of an effective measurement length of 25 mm, a strain of 0.5%, a frequency of 1 Hz, and a heating rate of 3°C / min. The tanδ peak temperature was determined from the peak detected by the automatic measurement of the RSI Orchestrator (manufactured by TA Instruments Inc., product name).

[0083] (8) tanδ peak height The tanδ value at the tanδ peak temperature range of -20 to 60°C, obtained in (7) above, was defined as the tanδ peak height for -20 to 60°C.

[0084] [Method for evaluating the properties of films, etc., using hydrogenated block copolymer compositions] (1) Tensile modulus Measurements were performed using the film prepared in the "Production of Films Containing Hydrogenated Block Copolymer Compositions" described later. In accordance with JIS K6251, a No. 5 dumbbell-shaped piece of film was punched out as a test specimen, and measurements were taken at a tensile speed of 200 mm / min and a chuck distance of 60 mm.

[0085] ((2) Stress relaxation rate) Measurements were performed using the film prepared in the "Production of Films Containing Hydrogenated Block Copolymer Compositions" described later. A No. 5 dumbbell-shaped piece of film was punched out as a test specimen. After stretching to 50% at a tensile speed of 50 mm / min and a chuck distance of 60 mm, the 50% stretch was maintained for 5 minutes. The test force T1 (N) immediately after 50% stretching and the test force T2 (N) after 5 minutes were measured, and the stress relaxation rate was calculated as 100 - (T2 / T1) × 100. ((3) Film formability) The evaluation was performed using the film prepared in the "Production of Films Containing Hydrogenated Block Copolymer Compositions" described later. Measurements were taken at four points at 5cm intervals along a 20cm section in the center of the film in the TD direction. The maximum, minimum, and average thicknesses were measured, and a score was assigned based on the thickness variation ((maximum thickness - minimum thickness) / average thickness) × 100 (%) and the results of the appearance evaluation, according to the following evaluation criteria. A higher score indicates better film formation performance. <Evaluation Criteria> 5: Film deposition is possible with a thickness variation of 10% or less. 4: Film deposition is possible with thickness variations of more than 10% but less than or equal to 20%. 3: Film deposition is possible with thickness variations of more than 20% but less than 30%. 2: Film deposition is possible with a thickness variation of 30% or more. 1. Film formation is unstable, and occasionally holes are formed on the film due to poor film formation. (Difficult to form film)

[0086] (4) Adhesion during installation work) The evaluation was performed using tapes prepared in the "Manufacturing of Tapes Containing Hydrogenated Block Copolymer Compositions" described later. A SUS plate measuring 20 mm thick, 25 mm wide, and 100 m long was subjected to a curved surface with a radius of curvature of 20 m along its longitudinal direction. Tape, with the support layer removed, was applied to the adhesive side under pressure and left for one day at 23°C and 50% RH. The peeling of the tape from the bent edges of the base material was visually observed and evaluated on a 5-point scale according to the evaluation criteria below. A higher evaluation score indicates better adhesion (flexibility) during installation. <Evaluation Criteria> 5: No peeling 4: Slight peeling present 3: Slight peeling present 2: Peeling present 1: Significant peeling

[0087] ((5) Long-term adhesive stability) The evaluation was performed using tapes prepared in the "Manufacturing of Tapes Containing Hydrogenated Block Copolymer Compositions" described later. The tape was cut into strips 50 mm wide and 250 mm long to create tape test pieces. A 60mm diameter stainless steel cylinder was placed perpendicular to the surface of a stainless steel plate. Tape test pieces were attached around the joint under conditions of temperature: 23±2℃ and humidity: 50±5%RH. After being left for up to 120 hours under conditions of temperature: 60±2℃ and humidity: 50±5%RH, the appearance of the adhesive tape was visually observed, and the time until delamination occurred was evaluated according to the following evaluation criteria. A higher evaluation value indicates better long-term adhesion stability (stress relaxation). <Evaluation Criteria> 4: No floating for over 120 hours 3. Floating occurred between 72 hours and less than 120 hours. 2: A float occurred between 24 hours and less than 72 hours. 1: Floating occurred within 24 hours ((6) Thickness of film, etc.) The average thickness measured in (3) above was used as the thickness of the film, etc.

[0088] [Manufacturing of hydrogenated block copolymers] (Preparation of hydrogenated catalyst) In the examples and comparative examples described later, the hydrogenation catalyst used to produce the hydrogenated block copolymer was prepared by the following method. A reaction vessel equipped with a stirring device was purged with nitrogen, and 1 liter of dried and purified cyclohexane was charged into it. Next, 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added. While stirring thoroughly, an n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was reacted at room temperature for approximately 3 days. This yielded a hydrogenation catalyst.

[0089] (Hydrogenated block copolymer) The hydrogenated block copolymers (a)-1 to (a)-14 and (a)-A to (a)-F, which constitute the hydrogenated block copolymer composition, and (b)-1 to (b)-7 were prepared as follows.

[0090] [Manufacturing Example 1] (Hydrogenated block copolymer (a)-1) Batch polymerization was carried out using a tank-type reactor (internal volume 10L) equipped with a stirring device and jacket. First, a cyclohexane solution (20% by mass concentration) containing 5 parts by mass of styrene was added. Next, 0.066 parts by mass of n-butyllithium per 100 parts by mass of total monomer, 1.20 moles of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as "TMEDA") per mole of n-butyllithium, and 0.04 moles of sodium-t-pentoxide per mole of n-butyllithium were added, and polymerization was carried out at 60°C for 1 hour. Next, a cyclohexane solution (20% by mass) containing 40 parts by mass of butadiene and 50 parts by mass of styrene was added, and polymerization was carried out at 80°C for 2 hours. Finally, a cyclohexane solution (20% by mass) containing 5 parts by mass of styrene was added, and polymerization was carried out at 65°C for 1 hour. After that, methanol was added to stop the polymerization reaction. The block copolymer obtained as described above had a styrene content of 60% by mass, a polystyrene block content of 10% by mass, a vinyl bond content of 48% by mass, and a weight-average molecular weight of 120,000. Furthermore, the hydrogenation catalyst prepared as described above was added to the obtained block copolymer at a concentration of 100 ppm (Ti-based) per 100 parts by mass of the block copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 65°C. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer to 100 parts by mass of the block copolymer to obtain hydrogenated block copolymer (a)-1. The hydrogenation rate of the obtained hydrogenated block copolymer (i)-1 was 98%. Other physical properties are shown in Table 1.

[0091] <Manufacturing Examples 2-21, A-F: Hydrogenated Block Copolymers (a)-2-(a)-11, (a)-14, (a)-A-F, (b)-1-(b)-7> In the method for producing the hydrogenated block copolymer (a)-1, the polymerization method and hydrogenation conditions were adjusted to produce (a)-2 to (a)-11, (a)-14, (a)-A to (a)-F, and (b)-1 to (b)-7. Their physical properties are shown in Tables 1 to 4 below.

[0092] (Hydrogenated block copolymer (a)-12) Batch polymerization was carried out using a tank-type reactor (internal volume 10L) equipped with a stirring device and jacket. First, a cyclohexane solution (20% by mass) containing 10 parts by mass of styrene was added. Next, 0.066 parts by mass of n-butyllithium per 100 parts by mass of total monomer, 1.20 moles of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as "TMEDA") per mole of n-butyllithium, and 0.04 moles of sodium-t-pentoxide per mole of n-butyllithium were added, and polymerization was carried out at 60°C for 1 hour. Next, a cyclohexane solution (20% by mass) containing 40 parts by mass of butadiene and 50 parts by mass of styrene was added, and polymerization was carried out at 80°C for 2 hours. After that, methanol was added to stop the polymerization reaction. The block copolymer obtained as described above had a styrene content of 60% by mass, a polystyrene block content of 10% by mass, a vinyl bond content of 48% by mass, and a weight-average molecular weight of 120,000. Furthermore, the hydrogenation catalyst prepared as described above was added to the obtained block copolymer at a concentration of 100 ppm (Ti-based) per 100 parts by mass of the block copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 65°C. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer to 100 parts by mass of the block copolymer to obtain hydrogenated block copolymer (a)-12. The hydrogenation rate of the obtained hydrogenated block copolymer (i)-12 was 98%. Other physical properties are shown in Table 2.

[0093] (Hydrogenated block copolymer (i)-13) Batch polymerization was carried out using a tank-type reactor (internal volume 10L) equipped with a stirring device and jacket. First, a cyclohexane solution (20% by mass) containing 10 parts by mass of styrene was added. Next, 0.079 parts by mass of n-butyllithium per 100 parts by mass of total monomer, 1.20 moles of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as "TMEDA") per mole of n-butyllithium, and 0.04 moles of sodium-t-pentoxide per mole of n-butyllithium were added, and polymerization was carried out at 60°C for 1 hour. Next, a cyclohexane solution (20% by mass) containing 18 parts by mass of butadiene and 22 parts by mass of styrene was added and polymerization was carried out at 60°C for 2 hours. Then, a cyclohexane solution (20% by mass) containing 50 parts by mass of butadiene was added and polymerization was carried out at 60°C for 2 hours. After that, methanol was added to stop the polymerization reaction. The block copolymer obtained as described above had a styrene content of 32% by mass, a polystyrene block content of 10% by mass, a vinyl bond content of 66% by mass, and a weight-average molecular weight of 120,000. Furthermore, the hydrogenation catalyst prepared as described above was added to the obtained block copolymer at a concentration of 100 ppm (Ti-based) per 100 parts by mass of the block copolymer, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 65°C. Next, 0.3 parts by mass of octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate was added as a stabilizer to 100 parts by mass of the block copolymer to obtain hydrogenated block copolymer (i)-13. The hydrogenation rate of the obtained hydrogenated block copolymer (i)-13 was 98%. Other physical properties are shown in Table 2.

[0094] [Table 1]

[0095] [Table 2]

[0096] [Table 3]

[0097] [Table 4]

[0098] [Examples 1-54 and Comparative Examples 1-6] [Production of films containing hydrogenated block copolymer compositions] The hydrogenated block copolymers (a)-1 to (a)-14, (a)-A to F, (b)-1 to (b)-7, and the components (c)-1 to (c)-4 listed below were dry-blended and supplied to the extruder in the composition (mass ratio) shown in Tables 4 to 11 below. Then, each layer was supplied to the extruder in the proportions shown in Tables 5 to 12 below to produce the final film thickness of each layer, and the film was manufactured. Films of Examples 1-54 and Comparative Examples 1-6 were produced by co-extrusion molding using a multilayer T-die extruder (PLABOR, manufactured by Plastics Engineering Laboratory Co., Ltd.) at an extrusion temperature of 200°C and a die temperature of 230°C, thereby integrating each layer. The films of Examples 45-54 are laminates containing a layer (I) containing a hydrogenated block copolymer (a) and a resin composition layer (II).

[0099] [Manufacturing of tapes containing hydrogenated block copolymer compositions] Using the films of the above-mentioned examples and comparative examples as the base layer, the adhesive layer was prepared in accordance with the method shown in

[0058] of Japanese Patent Application Publication No. 2023-150863, and a film (tape) having the configuration of a support layer / adhesive layer (10 μm) / base layer was manufactured in accordance with the film manufacturing method shown in

[0059] of Japanese Patent Application Publication No. 2023-150863. Specifically, the above-mentioned acrylic polyol resin (Hitaloid® D1002, manufactured by Hitachi Chemical Co., Ltd., with a hydroxyl value of 200 mg KOH / g) was mixed with 100 parts by mass of caprolactone polyol (Praxel® FM1D, manufactured by Daicel Corporation, with a molecular weight of 358) at a ratio of 16.3 parts by mass of caprolactone polyol (HDI, manufactured by Asahi Kasei Corporation, with a ratio of 51.2 parts by mass of hexamethylene diisocyanate (HDI) (Duranate® TPA100, manufactured by Asahi Kasei Corporation) and 5.8 parts by mass of a weather-resistant additive. This mixture was used as a composition for forming an adhesive layer. A film (tape) having the structure of a support layer / adhesive layer (10 μm) / base layer was obtained by extruding the film material of the above-mentioned example and comparative example as a base layer onto one side of a support layer (Mitsubishi Chemical Corporation's "Diafoil (registered trademark) T100-25" (polyester resin film, 25 μm)) and laminating it with a cast roll (extrusion lamination).

[0100] (Olefin resin or olefin elastomer (c)) <Component (c)-1> Olefin-based resin: Polypropylene resin PC630A (manufactured by Sun Allomer Co., Ltd.) <Component (c)-2> Olefin-based elastomer: vistamaxxx 6102FL (manufactured by ExxonMobil Chemicals) <Component (c)-3> Olefin resin: Ethylene-vinyl acetate copolymer resin Evaflex V5714C (manufactured by Mitsui Dow Polychemicals) <Component (H)-4> Olefin-based resin: Low-density polyethylene Suntech L2340 (manufactured by Asahi Kasei Corporation) <Component (H)-5> Olefin-based resin: Polypropylene resin PM801A (manufactured by Sun Allomer Co., Ltd.)

[0101] [Press-formed sheet manufacturing] The hydrogenated block copolymers (a)-1 to (a)-14, (a)-A to (a)-F, and (b)-1 to (b)-7, prepared as described above, were each rolled out individually using a 4-inch roll at 180°C, and then pressed using a hydraulic press at 200°C and 100 kg / cm². 2 Press molding was performed to produce a 2mm thick press-formed sheet.

[0102] The following items were evaluated for Examples 1-54 and Comparative Examples 1-6. The evaluation results are shown in Tables 5-12. (1) Tensile modulus ((2) Stress relaxation rate) ((3) Film formability) (4) Adhesion during installation work) ((5) Long-term adhesive stability)

[0103] [Table 5]

[0104] [Table 6]

[0105] [Table 7]

[0106] [Table 8]

[0107] [Table 9]

[0108] [Table 10]

[0109] [Table 11]

[0110] [Table 12]

[0111] When the thickness was kept constant at 150 μm, higher flexibility tended to result in better adhesion during installation. On the other hand, thicknesses of 1000 μm or less tended to result in good adhesion, while thicknesses of 50 μm or more tended to result in good film formation.

[0112] In single-layer structures, higher stress relaxation properties tended to correlate with higher long-term bonding stability. Furthermore, in multi-layer structures, higher stress relaxation properties in the layer containing the hydrogenated block copolymer (I) tended to correlate with higher long-term bonding stability.

[0113] Furthermore, in a comparison between manufacturing example 4 and manufacturing example 1, manufacturing example 1 tended to have higher blocking resistance for the hydrogenated block copolymer (a) pellets.

[0114] Furthermore, Examples 45-49 tended to have less film-to-film adhesion and better unwinding performance during film formation compared to Example 36.

[0115] (Example 55 and Comparative Examples 7-8: Manufacturing of Noise Reduction Film) Under the same conditions as described above for the production of films containing hydrogenated block copolymer compositions, films were prepared according to the compositions (mass ratios) and formulation conditions of Example 55 and Comparative Examples 7-8 as shown in Table 13.

[0116] [Table 13]

[0117] (Method for measuring noise from film) In an anechoic chamber with air conditioning, the films (200mm x 300mm) manufactured in Example 55 and Comparative Examples 7-8 were fixed with tape near the air conditioning outlet so that the airflow from the air conditioner hit them perpendicularly. The airflow from the air conditioner hitting the film was confirmed to be 1.6 m / s. The noise generated by the film's movement in the wind was recorded for 15 seconds using a microphone and analyzed to measure the time-averaged sound pressure level. (Measurement frequency range: 200-10000 Hz (1 / 3 octave band, Z-weighting, measurement temperature: 23°C, measurement humidity: 57%)) Figure 1 shows the sound pressure level measurement results at each frequency for the film created under the above conditions. Example 55, which contains the hydrogenated block copolymers (a) and (b) of this embodiment as constituent components, exhibits a lower sound pressure level across a wide frequency range compared to Comparative Examples 7 and 8, which do not contain them. In other words, applying the hydrogenated block copolymers (a) and (b) of this embodiment to film applications can reduce the sound generated from the film itself due to bending or other actions. Furthermore, because the hydrogenated block copolymers (a) and (b) of this embodiment are included as constituent components, they exhibit high flexibility and high stress relaxation properties, which facilitates film application and prevents lifting during long-term application. [Industrial applicability]

[0118] The hydrogenated block copolymer and its composition according to the present invention have industrial applicability in fields such as automotive parts, building materials, medical device materials, various containers such as food packaging containers, home appliances, industrial parts, and toys.

Claims

1. It contains vinyl aromatic monomer units and conjugated diene monomer units, Hydrogenated block copolymer (a) that satisfies the following conditions (1) to (4); <Condition (1)>: In the hydrogenated block copolymer (i), the content of polymer block (a) mainly composed of vinyl aromatic monomer units is 12% by mass or less. <Condition (2)>: The weight-average molecular weight (Mw) of the hydrogenated block copolymer (a) is 250,000 or less and 30,000 or more. <Condition (3)>: The hydrogenated block copolymer (a) contains at least one hydrogenated copolymer block (b) consisting of vinyl aromatic monomer units and conjugated diene monomer units, and the content of hydrogenated copolymer block (b) in the hydrogenated block copolymer (a) is 25% by mass or more. <Condition (4)>: The hydrogenated block copolymer (a) has a tanδ peak between 0 and 40°C in viscoelasticity measurement (1 Hz).

2. The hydrogenated block copolymer (i) according to claim 1, wherein the content of hydrogenated copolymer block (b) in the hydrogenated block copolymer (i) is 40% by mass or more and 97% by mass or less.

3. A hydrogenated block copolymer (a) according to claim 1, A hydrogenated block copolymer (b) containing vinyl aromatic monomer units and conjugated diene monomer units, and / or an olefin resin or olefin elastomer (c), The hydrogenated block copolymer (b) satisfies the following condition (5): A hydrogenated block copolymer composition in which the mass ratio ((a) / ((b)+(c))) of the content of the hydrogenated block copolymer (a) to the total content of the hydrogenated block copolymer (b) and the olefin resin (c) is 5 / 95 to 95 / 5; <Condition (5)> The hydrogenated block copolymer (b) contains at least one polymer block (a) mainly composed of vinyl aromatic monomer units, and the content of the polymer block (a) mainly composed of vinyl aromatic monomer units in the hydrogenated block copolymer (b) is greater than 12% by mass.

4. The hydrogenated block copolymer composition according to claim 3, wherein the mass ratio ((a) / ((b)+(c))) of the content of the hydrogenated block copolymer (a) to the total content of the hydrogenated block copolymer (b) and the olefin resin or olefin elastomer (c) is 40 / 60 to 80 / 20.

5. A hydrogenated block copolymer (a) according to claim 1 contains 5% by mass or more, The tensile modulus is 500 MPa or less. A film with a thickness of 20 μm or more and 2000 μm or less.

6. The following conditions (7) and (8) must be met, A laminate comprising a layer (I) and a resin composition layer (II); <Condition (7)>: The layer (I) contains the hydrogenated block copolymer (a) described in claim 1, <Condition (8)>: The outermost or innermost layer contains 95% by mass or more of olefin resin or olefin elastomer (c).

7. A hydrogenated block copolymer (a) according to claim 1 contains 20% by mass or more, The tensile modulus is 500 MPa or less. A film with a thickness of 50 μm or more and 1000 μm or less.

8. A layer (I) comprising the hydrogenated block copolymer (a) described in claim 1, A resin composition layer (II) and, A laminate with a thickness of 300 μm or less.

Citation Information

Patent Citations

  • Waterproof airtight pressure sensitive adhesive double coated tape

    JP2006299071A

  • Surface protection film

    JP2023150863A

  • Hydrogenated copolymer

    WO2003035705A1

  • Composition and molded body

    WO2022270581A1